Changes of the chlorogenic acid, caffeine, gama-aminobutyric acid (GABA) and antioxdant activities during germination of coffee bean (Coffea arabica) - Kim, Yeokyeong; Jhon, Yeongyil Kim; Deok-Young (Emirates Journal of Food and Agriculture, 2018)
This study was carried out to identify changes in functional materials during the germination of coffee seeds. Chlorogenic acid (CGA), caffeine, and g-aminobutyric acid (GABA) was assayed by HPLC method while germinating coffee beans for 20 days. The contents of total phenolic compounds and total flavonoid compounds were measured by colorimetric method. Antioxidant activity was measured by both 2,2-diphenyl-2-pycryl hydrazyl (DPPH) radical scavenging activity assay and 2,2’-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS•+) assay method. It was found that CGAs (5-caffeoylquinic acid (CQA), 4-CQA, 3-CQA), caffeine, and GABA increased and then decreased during germination. There were no significant changes in total phenolics, total flavonoids and antioxidant activities. Especially, all of the major isomers of CGA increased to the highest value at 10 days of germination, and GABA also increased significantly at the early stage of germination. This study showed that coffee beans changed into more functional food materials by germination and showed maximum functionality in appropriate germination conditions.